Anti-Aging Effect of Nigella Sativa Fixed Oil on D-Galactose-Induced Aging in Mice - Mahdieh Jafari Shahroudi; Soghra Mehri; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2017)
Objectives: Aging is an unconscious and gradual process that can lead to changes in biological systems. Induction of oxidative stress and apoptosis, hepatotoxicity and neurotoxicity are involved in the aging process. Regarding the antioxidant property of black seed oil, the aim of this study was to evaluate the anti-aging effect of Nigella sativa (N. sativa) oil on d-galactose-induced aging in mice. Methods: For induction of aging, D-galactose (500 mg/kg, subcoutaneously SC) was administrated to male mice for 42 days. Animals were treated with D-galactose alone or with b lack seed oil (0.1, 0.2, 0.5 mL/kg, intraperitoneally (ip)). Additionally, vitamin E (200 mg/kg) was used as a positive control. At the end of treatment, the malondialdehyde (MDA) and the glutathione (GSH) contents in brain and liver tissues were measured. Also, enzymes in serum, including aspartate aminotransferase (AST) and alanine amino transferase (ALT), were determined. The levels of the proteins Bax, Bcl2, caspase-3 (pro and cleaved) in brain and liver tissues were evaluated. Results: Administration of D-galactose (500 mg/kg, SC) for 42 days increased serum levels of ALT and AST, as well as the MDA content, in brain and liver tissues, but decreased the GSH content. Additionally, the levels of apoptotic proteins, including Bax, procaspase-3 and caspase-3 cleaved, were markedly increased. N. sativa oil (0.1 and 0.2 mL/kg) diminished the levels of the biochemical markers ALT and AST. Administration of black seed oil (0.1, 0.2 and 0.5 mL/kg) reduced lipid peroxidation and at doses 0.1 and 0.2 mL/kg significantly recovered the GSH content. The oil decreased Bax/Bcl2 levels and at 0.1 mL/kg down-regulated the expressions of caspase-3 (pro and cleaved) proteins in brain and liver tissues. Conclusion: Through its antioxidant and anti-apoptosis properties, black seed oil exhibited an anti-aging effect in a model of aging induced with D-galactose.